2006
DOI: 10.1016/j.ydbio.2005.10.033
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans histone deacetylase HDA-1 is required for cell migration and axon pathfinding

Abstract: Histone proteins play integral roles in chromatin structure and function. Histones are subject to several types of posttranslational modifications, including acetylation, which can produce transcriptional activation. The converse, histone deacetylation, is mediated by histone deacetylases (HDACs) and often is associated with transcriptional silencing. We identified a new mutation, cw2, in the Caenorhabditis elegans hda-1 gene, which encodes a histone deacetylase. Previous studies showed that a mutation in hda-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…In the vulva, hda-1 knockdown has been shown to cause a weak Muv phenotype in combination with mutations in any one of the class A and class B SynMuv genes (Lu and Horvitz 1998; Solari and Ahringer 2000). Subsequently, a similar phenotype was reported in hda-1 mutants alone (Dufourcq et al 2002; Zinovyeva et al 2006), although the SynMuv interaction was not observed (Dufourcq et al 2002). In addition, vulval cells in hda-1 animals fail to migrate and form ectopic invaginations (Dufourcq et al 2002).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In the vulva, hda-1 knockdown has been shown to cause a weak Muv phenotype in combination with mutations in any one of the class A and class B SynMuv genes (Lu and Horvitz 1998; Solari and Ahringer 2000). Subsequently, a similar phenotype was reported in hda-1 mutants alone (Dufourcq et al 2002; Zinovyeva et al 2006), although the SynMuv interaction was not observed (Dufourcq et al 2002). In addition, vulval cells in hda-1 animals fail to migrate and form ectopic invaginations (Dufourcq et al 2002).…”
supporting
confidence: 69%
“…HDA-1 (HDAC1), a catalytic subunit of NURD, is required for embryogenesis, gonadogenesis, germ cell formation, neuronal axon guidance, and vulval development (Dufourcq et al 2002; Zinovyeva et al 2006). In the vulva, hda-1 knockdown has been shown to cause a weak Muv phenotype in combination with mutations in any one of the class A and class B SynMuv genes (Lu and Horvitz 1998; Solari and Ahringer 2000).…”
mentioning
confidence: 99%
“…As the cortex develops, all newly generated neurons migrate past the older neurons to populate the cortical plate just below the marginal zone in a classical inside-out pattern (16). Given the known roles of HDAC1 and HDAC2 in regulating cell cycle and migration (17)(18)(19), it is interesting to see loss of HDAC1 and HDAC2 not overtly affecting migration. Mutant migrating neurons along radial glial fibers showed a moderate displacement compared with wild-type controls, however, the most pronounced phenotype was the overall lack of mature neurons after deletion of HDAC1 and HDAC2, espe- cially those born at E14.5.…”
Section: Discussionmentioning
confidence: 99%
“…Because HDACs are involved in regulation of the cell cycle (17) and have been shown to control cell migration (18,19), we speculated that the observed phenotypes could be because of inefficient neuronal migration and/or defective progenitor specification. Development of the cerebral cortex is an intricate process that involves sequential neurogenesis and migration.…”
Section: Neuronal Migration Is Intact In Cns Deletion Of Hdac1 and Hdmentioning
confidence: 99%
“…The hda-1 mutation produced a highly penetrant, uncoordinated locomotion phenotype with severe defects in axon pathfinding, fasciculation of the nerve cord and neuronal cell migration (Zinovyeva et al, 2006).…”
Section: Hdac1 and Hdac2 In Heart Developmentmentioning
confidence: 99%